Four views on moving beyond the Bible to theology - Meadors, Gary T., 1945-; Kaiser, Walter C., Jr. (Walter Christian), 1933- (Grand Rapids, Mich. : Zondervan, 2009)
Guides readers to consider and evaluate the various ways Christians apply biblical texts to contemporary questions. Four different scholars present their preferred interpretive models in point-counterpoint style, and three additional authors follow with their own perspectives on questions of moving from Scripture to theology. --from publisher description.
A principilizing model / Walter C. Kaiser Jr. -- A redemptive-historical model / Daniel M. Doriani -- A drama-of-redemption model / Kevin J. Vanhoozer -- A redemptive-movement model / William J. Webb.
Includes bibliographical references (pages 349-351) and indexes.
Keywords: Bible -- Use; Theology -- Methodology; Bible -- Hermeneutics